An accurate determination of the phase center position of transitions into 2-dimensional regions - Uyguroglu, Rasime; Embais, Khadija (Wiley, 2018)
Correct estimation of the phase centers of the input and output ports is important in Rotman-type bootlace lens applications. Any shift in the position of the phase center of a port used as a transition between the feed lines and the 2-dimensional region will cause phase errors, which will create adverse effects on the radiation patterns. This paper introduces a method for determining the phase centers of the transitions radiating into parallel plate regions. A study has been conducted for linearly tapered and multistep transitions (ie, radiators). The results of the study show that the estimated phase centers are displaced from the aperture of the transitions. This displacement is smaller for the multistep transitions compared with the linearly tapered transitions. The simulation results of these transitions also show that, the use of the estimated phase center position reduces the phase errors significantly over wide coverage angles. The results also show that the phase errors do not change with the distance from the aperture. On the other hand, phase errors varies with frequency. These errors are smaller for the stepped transitions compared with the linearly tapered transitions. A separate simulation study of radiation patterns of a linear array fed by a Rotman lens has shown that deterioration occurs in sidelobes and minima levels and a small shift in the off-axis beam positions when short transitions are used without phase center position correction.
Keywords: 2-dimensional region; far field region; linear taper; multiple beam; multistep transition; parallel plate region; phase center